O ensino das estratégias de compreensão leitora: uma proposta com livros de literatura infantil - Silva, Joice Ribeiro Machado da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The present research has its origin in challenges experienced by me as a teacher with the task of educating readers, what motivated seeking solutions by means of study and research. It has as assumption that reading is a complex process to be developed and it is not reduced to decoding texts. The central problem consists in finding methodologies that assure an education of a competent reader, primary function of Elementary School. The aims of this research is to verify how a systematic work on the teaching of reading strategies with children's books literature helps to advance the understanding of the literary text, overcoming misguided practices often used in daily school to teach reading, such as: oral reading, quizzes, study vocabulary and exclusive use of the textbook. The methodology consisted of theoretical research and action research, applied to a 5th grade Elementary School class, in a public school of the city of Marilia/SP, where I worked as a classroom teacher. The research covered the following phases: initial diagnostic, three stages of applying the U.S. methodology, for teaching reading strategies, being the last evaluation....

A presente pesquisa tem sua origem nos desafios por mim experimentados como professora na tarefa de formar leitores, o que motivou a busca de soluções por meio de estudos e de investigações. Tem como pressuposto que a leitura é um processo complexo a ser desenvolvido e não se reduz à decodificação de textos. O problema central consiste em encontrar metodologias que garantam a formação de leitor competente, função precípua da escola de Ensino Fundamental. O objetivo dessa pesquisa é verificar como um trabalho sistematizado sobre o ensino das estratégias de leitura com livros de literatura infantil contribui para o avanço na compreensão do texto literário, superando práticas equivocadas frequentemente utilizadas no cotidiano escolar para se ensinar a ler, tais como: leitura oral, questionários, estudo do vocabulário e uso exclusivo do livro didático. A metodologia utilizada constou de pesquisa teórica e pesquisa-ação, aplicada em uma turma de 5º ano do Ensino Fundamental de uma escola pública municipal da cidade de Marília/SP, na qual atuei como professora da turma...
Keywords: Educação; Leitura - Estudo e ensino; Literatura infanto-juvenil; Leitores - Reação critica; Education